The crusades : Islamic perspectives - Hillenbrand, Carole (Edinburgh University Press, 1999)
"This is not a chronological survey of the events of the period 1099 to 1291 and even beyond, for that has already been done several times. Instead, this is a general book intended to introduce some of the wider aspects of the history of the Crusades from the Muslim side. Accordingly, as a deliberate policy, an attempt is made here to view the phenomenon of the Crusades entirely through the prism of medieval Muslim sources. This naturally involves bias, but such a bias is salutary given the cumulative impact of centuries of Eurocentric scholarship in this field and it should help to create a more balanced picture of this fascinating and momentous period of Christian/Muslim confrontation and interaction." "The text is accompanied by well over 500 illustrations of medieval Islamic art which provide a visual reinforcement for this attempt to view the Crusades from 'the other side'."--Jacket.